Influence of depression and loneliness on suicidal behaviour among public university students in Malaysia - Norazizi, Nur Dini Kamilia; Che Amat, Muhammad Asyraf; Mohammad Hanafi, Nor Hafizah; Firman; Salam, Syahrul Nizam (Universiti Putra Malaysia, 2024)
Suicide is a serious and curable public health issue that is alarming towards early adults like university students who are undergoing personal and social phase changes and pressures. This study investigates the influence of depression and loneliness on the suicidal behaviour of public university students in Malaysia. The quantitative study involved 406 public university students in Malaysia, including early teens aged 20 years and below and adults aged 40 years and above. Three instruments were used: Suicide Behaviours Questionnaire-Revised (SBQ-R), Beck Depression Inventory (BDI), and UCLA Loneliness Scale Version 3. Data analysis involves examining basic statistical information. For this study, a stratified and proportional random selection method was used. The results indicated that public university students in Malaysia generally exhibited minimal levels of depression, loneliness, and suicidal behaviour. Depression and loneliness emerged as significant positive predictors influencing suicidal behaviour, accounting for 49.3% of the variance, while loneliness contributed to 0.3%. These non-significant findings suggest that overall, the mental well-being of the students is good. The study also highlights the role of cultural and societal factors unique to Malaysia in promoting positive mental health outcomes.